Threatened Herbal Heritage of Tribal Land Jharkhand - Jaipuriar, M. K. (Indian Forester, 2003)
The present paper deals briefly about threatened herbal flora of Jharkhand. The threatened status has been classified as suggested by IUCN for conservation-prone plants. Eight species and 7 families have been listed under endangered class, while 18 species of13 families bave been included in vulnerable category. Indeterminate category has 16 species spread among 10 families. Under endemic category are listed 30 species of24 families. It has been suggested that process should be started for the creation of ’herbal sanctuaries’ at different places to conserve the gent pool of herbs of Jharkhand.